Pengaruh Media Sosial Tiktok dan Lingkungan Sosial Terhadap Gaya Hidup Remaja Kota Banda Aceh - Varita, Nirma; Nisa, Uswatun; Saleh, Rahmat (SOURCE : Jurnal Ilmu Komunikasi, 2024)
Teenagers as social media users tend not to be ready to choose useful web activities and are also more often affected by the social environment. All of that will have an impact on the lifestyle of teenagers. This study aims to determine whether or not there is an influence of TikTok social media and social environment on the lifestyle of teenagers in Banda Aceh city. This study used quantitative methods, by distributing questionnaires to 269 respondents. The theory used in this research is the Stimulus Organism Response (S-O-R). From the F test analysis, social media  (X1) and social environment (X2) has a significance value of 0.001 which is smaller than 0.5, so both of them have a significant influence on the Lifestyle (Y). The t test analysis indicate that the social media variable (X1) has a t count value of 6.055> t table 1.986 and the social environment variable (X2) has a t count value of 3.460> t table 1.986, so that both variables X1 and X2 are proven to have a partial effect on the Lifestyle variable (Y). Then R Square test results show a value of 0.198 (20%), which means that the independent variables contribute as much as 20% to lifestyle variables. Social media variables contributed 0.164 (16.4%) and social environment variables contributed 0.94 (9.4%) to teenagers lifestyle. The results of this study show that there is about 80% contribution from other variables that affect the teenagers lifestyle, which can be investigated as further research. The results of this study give an idea for society about how exactly social media and social environment affect the lifestyle of adolescents.Keyword : Teenagers, lifestyle, social Media, Social Environment, TikTok